Hubungan Status Gizi, Asupan Bahan Makan Sumber Purin dengan Kadar Asam Urat pada Pasien Hiperuresemia Rawat Jalan di Rumah Sakit Tugurejo Semarang - Hana Silviana; Sufiati Bintanah; Joko Teguh Isworo (Jurnal Gizi, 2015)
Hyperurisemia is a disease that marked by sudden and recurrent attacks with a very painful pain as a result of high levels uric acid in the blood that exceed normal limits. Normal levels of uric acid for women is 2,4 to 5,7 mg/dl blood and for man is 3,4 to 7 mg/dl blood. The cause hyperuricemia is a metabolic disorder since birth, consumption of foods high purines, body weight, and the amount of alcohol. The general research purpose of this study is to determine the relationship of nutritional status and intake of purine source with uric acid levels of outpatientswith hyperuricemia in hospital Tugurejo Semarang.The type of reaserch is explanatory research with crossectional approach. The number of sample are 22 outpatients in hospitals Tugurejo Semarang. Univariate analysis will be undertakento present the frequency distribution data. The Shapiro-wilks test was used to analysis the normality distribution both of datas .Bivariate analysis to examine the relationship between two variables will be done by the pearson correlation test, and by the spearman rank test.The result of study showed there are 12 persons of samples (54,5%), are 51-70 years old.There are 8 persons of samples (36,4%) were yunior levelsof education and there are 12 persons of samples (54,5%) have the most fat of nutritional status. Based on the intake of purine source material feeding as many as 22 samples (100%). Uric acid levels by about 16 samples (72,7%)?.Statistical analysis showed the significant relationship (pv =0,000) between the nutritional status and the level of uric acid of blood. The study showed the significant relationship (pv =0,038), between the level of purine uric intake and the level of uric acid of blood.Key words : nutritional status, purine intake, level of uric acid